Evaluation of Nupro® Yeast Product in Diets for Broilers - Wang, Z.; Cerrate, S.; Coto, C.; Sacakli, P.; Yan, F.; Costa, F.G.P.; Waldroup, P.W. (International Journal of Poultry Science, 2009)
Two trials with identical experimental design were conducted approximately 20 months apart to evaluate the response of broiler chickens to the addition of NuPro®, a yeast product rich in nucleotides. In both trials, four dietary treatments were compared. The first treatment contained no NuPro®. For the second treatment, the diet with 2% NuPro® was fed only the first 7 days of life while for the third treatment, 2% NuPro® was fed for the first 14 d. For the fourth treatment, 2% NuPro® was fed for the first 7 days and also during the finisher period of 35-42 d of age. In both studies, each treatment was fed to six replicate groups of 60 male broilers of a commercial strain. Response to the addition of NuPro® varied between the two experiments. In the first study, addition of 2% NuPro® to the diet resulted in improvement in feed conversion. Response varied by age of bird and time during which the NuPro® was fed. At 7 d of age, there were no significant differences between birds that had been fed NuPro® and those fed the negative control diet. At 14 d of age, there were no significant differences in feed conversion among birds fed the various treatments, but feed conversion was numerically better for those birds that had been fed NuPro® for the first 7 or 14 d. At 35 d, birds that had been fed NuPro® for the first 7 d had significantly better feed conversion than those fed the control diet with birds fed NuPro® for the first 14 d being intermediate between these two groups. At 42 d, birds fed diets with 2% NuPro® for the first 7 d or for the first 7 d followed by feeding from 35-42 d had significantly lower feed conversion than those fed the control, with those fed NuPro® for the first 14 d being intermediate between these groups. However, in the second trial there was no significant effect of inclusion of NuPro on any of the parameters evaluated. There may be nutritional differences between batches of the product that influence the response of chicks.